ANALISA NILAI TUKAR PETANI DI PROVINSI RIAU - Rezi Abdurrahman; Lukman Hakim (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study was conducted to determine the factors that influence the farmer's exchange rate (the ratio of the price index received by farmers to the price index paid by farmers) in the food crops sub-sector in Riau Province. The data collected in this study is data published by the Central Statistics Agency of Riau Province. The data obtained were then analyzed using SPSS 22. The test results show that the level of expenditure has a negative and significant effect on the exchange rate of farmers in the food crop sub-sector, this can be seen from the value of tcount (-2.475) < ttable (2.44691) with a significant value of 0.048 < 0.05. Harvested area has a significant positive effect on the exchange rate of farmers in the food crop sub-sector, this can be seen from the value of tcount (4.441) < ttable (2.44691) with a significant value of 0.004 <0.05. Meanwhile, the food import variable has no significant effect on the exchange rate of farmers in the food crop sub-sector, this can be seen from the value of tcount (2.273) < ttable (2.44691) with a significant value of 0.063 > 0.05, with a value of Fcount (12.476) > Ftable , (4,35).